Training pre-service language teachers - Skela, Janez (ELOPE (Ljubljana), 2004)
This article considers some ways of tackling input in pre-service teacher training. First, it highlights the context and structure of a pre-service course currently provided by the Faculty of Arts, University of Ljubljana, Slovenia. Then it goes on to describe the process of designing a syllabus forthe course capitalizing on its methodology component which draws on a wide range of current refl ection-oriented models and approaches to teacher training. From these models, a teacher-training activities 'generator' is derived, which allows for the formation of many teacher-training procedures. It is argued that such methodology, besides giving trainees the opportunity to examine their attitudes, beliefs and assumptions, also echoes classroom practice.
Keywords: angleščina; metodika pouka; organizacija pouka; pedagoška praksa; učitelji; univezitetni študij; usposabljanje